Pelatihan Pemanfaatan Simulator Sistem Injeksi Sepeda Motor untuk Meningkatkan Kompetensi Motor Bakar Siswa SMK Bina Nusa Slawi - Firman Lukman Sanjaya; Faqih Fatkrurrozak; Syarifudin; Hasti Sulistia (Universitas Lancang Kuning, 2022)
SMK is a school that produces graduates who are competent and ready to work. However, the Covid-19 outbreak forced students to study at home so the competency of SMK graduates was less than optimal. Student competency improvement training is the solution to this problem. Training activities on the use of injection simulators at Bina Nusa Slawi Vocational School are one of the activities to increase student competency. This training was attended by 20 class XII students majoring in TBSM. This training was carried out through several stages, namely the preparation, implementation, and evaluation stages. The implementation stage starts with the pre-test session, material presentation, demonstration, and practicum. The final stage is training evaluation. The results of the evaluation of learning outcomes show that students' understanding of internal combustion engines and injection systems has increased compared to before attending the training. Evaluation of satisfaction shows that students are satisfied with the instructor's delivery method, the usefulness of the training, and the development and improvement of training in the future. This is proven by the average student assessment on the questionnaire, which is above 3.